Effect of slope and number of blades on Archimedes screw generator power output. (June 2019) - Dellinger, Guilhem; Simmons, Scott; Lubitz, William David; Garambois, Pierre-André; Dellinger, Nicolas
Abstract: A computational fluid dynamic (CFD) simulation of an Archimedes screw generator (ASG) was carried out in conjunction with laboratory-scale experiments to determine the effect of inclination angle and number of blades on ASG power production and performance. Good agreement was found between the model and experiment; the CFD model had relative errors in hydraulic efficiency of less than 2% in optimal cases. Both the experiments and CFD simulations were carried out for inclination angles between 10° and 38°. Afterwards CFD was used to simulate the effect of three different numbers of blades (3, 4 and 5) of an ASG with common design parameters. Overflow and gap leakage losses were found to increase at higher inclinations - these losses decreased with the addition of blades. For this particular ASG setup, the 5-bladed screw generated the most power. The 4 and 5-bladed screws had their highest efficiencies at inclination angles between 20° and 24.5°. The 3-bladed screw was found to have its highest efficiencies at comparatively lower inclination angles, with the simulations finding the optimal angle to be approximately 15.5°. Both CFD simulations and the experiments showed that overflow leakage started to happen much sooner at higher inclination angles, as expected. Highlights: Archimedes screw generators are simulated with computational fluid dynamics (CFD). Simulations successfully validated with laboratory screw performance data. CFD provides screw dynamics insights not available from experiments. In depth analysis shows moderate slope gives best screw efficiency. The effect of number of blades on efficiency was examined and results explained.